A1M/α1-microglobulin is proteolytically activated by myeloperoxidase, binds its heme group and inhibits low density lipoprotein oxidation - Cederlund, Martin; Deronic, Adnan; Pallon, Jan; Sørensen, Ole E.; Åkerström, Bo (Frontiers in Physiology, 2015)
α1-microglobulin (A1M) is a 26 kDa plasma and tissue protein with reductase activity and radical- and heme-binding anti-oxidative functions. In addition, exposure of A1M to hemoglobin has been shown to induce proteolytic elimination of a C-terminal tetrapeptide yielding a heme-degrading form, truncated A1M (t-A1M). Myeloperoxidase (MPO), a heme-containing enzyme that catalyzes the production of free radicals and hypochlorite, is released by neutrophils during the inflammatory response to bacterial infections. MPO-induced low density lipoprotein (LDL)-oxidation in blood has been suggested as a causative factor in atherosclerosis. In this study we have hypothesized that A1M interacts with MPO in a similar mode as with hemoglobin, and is a regulator of its activity. The results show that A1M is proteolytically cleaved, with formation of t-A1M, after exposure to MPO, and that t-A1M contains iron and heme-degradation products. The reaction is dependent of pH, time and concentration of substrates and a pH value around 7 is shown to be optimal for cleavage. Furthermore, A1M inhibits MPO- and hydrogen peroxide-induced oxidation of LDL. The results suggest that A1M may have a role as an inhibitor of the damaging effects of the neutrophil respiratory burst on bystander tissue components.